Hybrid Multi-Criteria Decision Framework for Prosumers Energy Storage Systems in Smart Grids - Marriam Liaqat; Muhammad Adnan; Mohaira Ahmad; Muhammad Sajid Iqbal; Faizan Ahmad; Sami Ud Din (IEEE Access)
Modern power systems encompass multiple prosumers, smart grid technologies, and renewable energy resources (RERs). These prosumer-based smart grids are facing the reliability issues that can be mitigated through the adoption of competitive storage technologies. A range of competitive storage technologies have been developed by scientists. However, the systematic selection of best storage technologies is still one of the main challenging research issues in the current literature. To fill this literature gap, this paper proposes a multi-criteria decision framework for energy storage selection in prosumer-based networks. First, a decision-making hierarchy was developed based on the three main criteria including energy flow management for prosumers, technical features, and sustainability. Under these criteria, various sub-criteria were identified. Second, multi-criteria decision making (MCDM) problem was solved for two cases using Analytic Hierarchy Process (AHP) and Preference Ranking Organization Method for Enrichment of Evaluations (PROMETHEE) methods separately. Third, a hybrid AHP and PROMETHEE method was proposed for the selection of an efficient storage system for prosumers based smart grid. Finally, a comprehensive outlook has been provided for prosumer energy storage evaluation. Findings revealed several implications for more accurate storage evaluation decision making. For instance, sensitivity analysis reveals that the lithium ion battery (LIB) has the first preference in AHP method, and the lead acid battery (LAB) has the first preference in PROMETHEE method. However, the second preference for AHP method was the LAB, and the second preference for PROMETHEE method was the LIB. Hence, separate application AHP and PROMETHEE offered a slightly different ranking. According to the proposed hybrid procedure, LIB was ranked as the first option by both AHP and PROMETHEE methods. As a result, the hybridization of AHP and PROMETHEE methods offered a more robust and unique solution to the storage selection problem as compared to the individual method. Storage evaluation decision making has several implications for prosumer-based power systems. In future, only a few storage alternatives would not meet the needs of the large scale emerging power systems, such as peer-to-peer networks. In this situation, the rapid and accurate ranking of various competitive storage alternatives would be a challenging problem. This study is valuable because it offers a comprehensive and flexible decision making tool for storage evaluation for prosumer-based smart grids. For instance, the proposed model can be evaluated with addition or removal of criteria and storage alternatives under different situations.